EPIDEMIOLOGY AND TREATMENT OF FUNGAL INFECTIONS IN ONCO-PEDIATRIC PATIENTS AT A REFERRAL HOSPITAL - Bitencourt, Jéssica Neves; Silva, Lillian Morais; Soares, Renata de Bastos Ascenço; Godoy, Cássia Silva de Miranda (Revista Unimontes Científica, 2021)
Aim: to identify the epidemiology of fungal infections in the pediatric service of a reference hospital for the treatment of cancer for 2016 to 2019, through the dispensing of antifungal drugs by the hospital pharmacy. Methods: Retrospective cohort analysis of 1.211 antifungal requests. Results and Discussion: 1.211 treatments with antifungal agents were performed in the period, with 71.9% of cases treated with empirical therapy, 64.1% of cases of mucocutaneous candidiasis and with the use of nystatin in 48.6% of cases. There were 114 episodes of IFIs, in which probable fungal pneumonia represented 40.4% of the therapeutic indications, based on suggestive tomographic images and clinical and epidemiological criteria in 40.3% of cases. Conclusions: There was an agreement between the epidemiology of fungal infections and the worldwide epidemiology, but there was disagreement between the therapies applied in the study hospital and the recent guidelines.